Electrocatalytic Reduction of Oxygen at Glassy Carbon Electrodes Coated with Diazonium‐derived Porphyrin/Metalloporphyrin Films. Issue 6 (13th May 2020) - Kudas, Zuleyha; Atmaca, Ufuk; Saruhan, Tuba; Celik, Murat; Ekinci, Duygu
Abstract: In this study, the influence of the film structure was investigated on the electrocatalytic oxygen reduction at GC electrodes covered with porphyrin and metalloporphyrin rings via the diazonium modification method. For that purpose, primarily, tetraphenylporphyrin (TPP) films on GC electrode surfaces were prepared by electroreduction of in situ generated diazonium salts of 5‐(4‐aminophenyl)‐10, 15, 20‐triphenylporphyrin (APP) and 5, 10, 15, 20‐tetrakis(4‐aminophenyl)porphyrin (TAPP) molecules. Next, the formation of metalloporphyrin films on the modified surfaces was accomplished through the complexation reactions of surface porphyrin rings with metal ions in the salt solutions containing Mn(II), Fe(III) and Co(II) ions. The resulting porphyrin and metalloporphyrin layers were identified with XPS and ICP‐MS. The electrochemical barrier properties of the films on GC surfaces were examined by cyclic voltammetry in K3 Fe(CN)6 aqueous solution. The electrocatalytic abilities of the resulting films were also investigated for the oxygen electrochemical reduction by employing cyclic voltammetry in PBS solutions saturated with oxygen. The results showed that the oxygen reduction potentials on modified GC electrodes were shifted to less negative potentials compared to that of bare GC electrode. Also, it was obtained that the oxygen reduction reaction was more effective on the GC electrodes modified with TPP rings by using TAPP molecules than those prepared by using APP molecules. Abstract :